Damaged RC beams strengthened with NSM CFRP rectangular rods under vibration in different constrain conditions. (15th October 2016) - Capozucca, R.; Domizi, J.; Magagnini, E.
Abstract: The strengthening of damaged reinforced concrete (RC) beams through near surface mounted (NSM) fiber reinforced polymers (FRPs) has been shown to be a suitable method in practice. Availability of this technique is based on maintaining the adhesion between FRP rods and the concrete surface of grooves, both undamaged and damaged by cracking of beams. Controlling the status of RC beams strengthened with NSM FRP rods may be carried out through non destructive experimental tests measuring dynamic parameters such as frequency values. This paper analyses experimental vibration of four RC beam models without strengthening and strengthened with NSM carbon-FRP rectangular rods after damage due to bending cracking of concrete by static tests. The investigation of vibration was carried out considering RC beams at different static loading damages in different constrain conditions: two beam models were studied assuming free-free end condition and the other two with hinge-hinge end condition. Envelope of Frequency Response Functions (FRFs) obtained through dynamic testing are shown in the paper and changes of frequency values are compared and discussed. Finally, a comparison between experimental and theoretical dynamic values obtained by finite element analysis is developed to verify the control of RC beams strengthened with NSM CFRP rods.